EXPERIMENTAL STUDY OF THE PHASE DIAGRAM OF CAMGSI2O 6-CAAL0.5SI2O6 SYSTEM AT 3.0 GPA - Surkov N.V.; Gartvich Yu.G.; Babich Yu.V. (My University, 2004)
Conclusions: (1) The results of the study of phase relations in the diopside-calcium Eskola molecule system have made it possible to plot a phase diagram for the diopside-calcium-CEM system at 3.0 GPa. (2) The new phase (α-diopside) detected in our experiments undergoes phase transformation into diopside under chilling. (3) The existence of α-diopside promotes new reactions and decreases melting temperatures in the diopside-calcium-CEM by ~ 200°C.